Mapping digital ecosystem for competitive advantage using technological advancements - Morande, Swapnil; Tewari, Veena (SAINTIS Publishing, 2023)
‘Digital Ecosystem’ is the interdependence of computer software, hardware, and digital services that play a significant role in fulfilling the organization’s objectives. It is a convergence of recent broadband adoption and technological advancement that has pushed the state-of-the-art technologies, and industrial commerce into a flux, for greater market penetration. One of the most significant advantages of the Digital Ecosystem includes mapping of consumer interest (with product or services) to gain a competitive advantage in the market. The research presents various tangible and intangible benefits received by the organization with the help of the Digital Ecosystem. In the future, customers are likely to align their buying behavior based on ‘Digital Ecosystems’ they prefer. The variables involved in buying behavior are complex as well as difficult to measure; hence the qualitative approach has been followed to integrate various aspects of the proposed study. This research is significant because the ‘Digital Ecosystem’ can be a part of a business strategy that can gauge customer requirements, enhance customer experience, and retain customer loyalty.